Semen analysis in precision farming in the 21st century - Soler, Carles; Valverde, Anthony (Agronomía Mesoamericana, 2023)
Introduction. Assisted reproduction of animals traces its origins in the domestication of livestock species useful to humans. The consequent artificial selection processes allowed the development of biotechnological techniques that contributed to the improvement of animal production capacities. Objective. To contextualize the seminal analysis in precision farming in the 21st century. Development. The visualization of spermatozoa under the microscope can be considered as the first step in the advent of reproductive biotechnology and the basis for the development of assisted reproductive techniques. With the improvement of microscopy methods, it was possible to characterize male gametes, which meant a significant advance in artificial insemination technology. The turning point marked by the development of sperm conservation techniques implied a substantive change in the development of these technologies in livestock species, either with cryopreserved or refrigerated semen. These methods are of high value in the case of threatened species since germplasm banks can be created for genetic conservation and rescue of species at risk of extinction. Semen analysis has been developed alongside with assisted reproduction techniques and today it is considered a relevant technique in animal reproduction biotechnology, which has been perfected through the advancement of science and technology, optical physics, and computing. Conclusion. Seminal analysis has undergone a paradigm shift by rejecting obsolete techniques of subjective evaluation of semen quality and adopting objective methods of semen evaluation, through the analysis of large volumes of data and motility, kinematics, morphometrics, morphological, and DNA fragmentation variables, which allow a better characterization of the ejaculates of breeders in artificial insemination centers.